2015
DOI: 10.7554/elife.09207
|View full text |Cite
|
Sign up to set email alerts
|

SPOP mutation leads to genomic instability in prostate cancer

Abstract: Genomic instability is a fundamental feature of human cancer often resulting from impaired genome maintenance. In prostate cancer, structural genomic rearrangements are a common mechanism driving tumorigenesis. However, somatic alterations predisposing to chromosomal rearrangements in prostate cancer remain largely undefined. Here, we show that SPOP, the most commonly mutated gene in primary prostate cancer modulates DNA double strand break (DSB) repair, and that SPOP mutation is associated with genomic instab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
184
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(197 citation statements)
references
References 35 publications
12
184
1
Order By: Relevance
“…SPOP mutations define a distinct and key molecular class of prostate cancer, with characteristic genomic alterations, patterns of genomic rearrangements, gene expression profiles and methylation patterns (Barbieri et al, 2012; Blattner et al, 2014; Boysen et al, 2015; Cancer Genome Atlas Research, 2015). SPOP mutations occur early in the natural history of prostate cancer solely as heterozygous missense mutations with dominant negative, selective loss of function towards the remaining wild-type allele (Baca et al, 2013; Boysen et al, 2015; Prandi et al, 2014; Theurillat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SPOP mutations define a distinct and key molecular class of prostate cancer, with characteristic genomic alterations, patterns of genomic rearrangements, gene expression profiles and methylation patterns (Barbieri et al, 2012; Blattner et al, 2014; Boysen et al, 2015; Cancer Genome Atlas Research, 2015). SPOP mutations occur early in the natural history of prostate cancer solely as heterozygous missense mutations with dominant negative, selective loss of function towards the remaining wild-type allele (Baca et al, 2013; Boysen et al, 2015; Prandi et al, 2014; Theurillat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These three genes are also in our CONIM gene list. Several other studies investigated relations between point mutations and CNA numbers in single cancer types: a higher number of CNAs has been reported in SPOP-mutated prostate cancer (Boysen et al, 2015). Lower CNA numbers have been detected in CASP8-mutated oral squamous cell carcinoma (Pickering et al, 2013) and in CTNNB1-mutated endometrial cancer (Kandoth et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the length distribution of CNAs reflects chromosomal interactions (Fudenberg et al, 2011). The observation that certain genes tend to be mutated in CNA-rich (TP53 and SPOP [Ciriello et al, 2013; Boysen et al, 2015]) or CNA-poor (CTCF and ARID1A [Ciriello et al, 2013]) cancers implies that, besides epigenetic factors, the genetic background of the cell influences CNA variation.…”
Section: Introductionmentioning
confidence: 99%
“…Concordant with this, SPOP- mutant tumors have been found to have among the highest androgen receptor transcriptional activity 5 . Importantly, it has been recently demonstrated that SPOP modulates DNA double strand break (DSB) repair, is associated with genomic instability, and sensitizes to DNA damaging agents such as PARP inhibitors 52 .…”
Section: Introductionmentioning
confidence: 99%